Juridical Analysis of Doctor's Criminal Liability in Medical Malpractice Cases - Heru Cahjono; Prija Djatmika; Setiawan Noerdajasakti (Faculty of Law, Universitas Pekalongan, 2023)
Medical malpractice is one of the crucial issues in the world of law and health because it involves patient safety and the criminal responsibility of medical personnel. In Indonesia, the complexity of proving the elements of negligence, the limitations of evidence, as well as the inconsistency between legal norms and professional ethics are the main challenges in enforcing the criminal liability of doctors. This study aims to analyse the criminal liability of doctors in medical malpractice cases, particularly the obstacles in proving the criminal element and its implications for criminal law reform in Indonesia. The approach used is normative juridical, through literature study, legislation, and analysis of court decisions. The results showed that proving the element of guilt in medical malpractice relies heavily on expert testimony and the judgement of professional institutions such as MKDKI and MKEK, which often leads to differences in legal interpretation. The case study of Tangerang District Court Decision No. 1324/Pdt.G/2021/PN.Tng highlights the weak integration between professional ethical mechanisms and the national criminal system. This research has implications for the need for regulatory reform through the establishment of a lex specialis regarding the criminal liability of medical personnel, as well as strengthening the application of restorative justice in medical dispute resolution. The originality of this research lies in the focus of juridical analysis on the obstacles to proving criminal elements and comparative application of law in the context of the Indonesian legal system, which so far has not been the main focus in the health law literature.